2005
DOI: 10.1038/sj.emboj.7600854
|View full text |Cite
|
Sign up to set email alerts
|

Transactivation of Schizosaccharomyces pombe cdt2+ stimulates a Pcu4–Ddb1–CSN ubiquitin ligase

Abstract: Cullin-4 forms a scaffold for multiple ubiquitin ligases. In Schizosaccharomyces pombe, the Cullin-4 homologue (Pcu4) physically associates with Ddb1 and the COP9 signalosome (CSN). One target of this complex is Spd1. Spd1 regulates ribonucleotide reductase (RNR) activity. Spd1 degradation during S phase, or following DNA damage of G2 cells, results in the nuclear export of the small RNR subunit. We demonstrate that Cdt2, an unstable WD40 protein, is a regulatory subunit of Pcu4-Ddb1-CSN ubiquitin ligase. cdt2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(122 citation statements)
references
References 39 publications
(74 reference statements)
4
113
0
4
Order By: Relevance
“…We favor the former model because there is strong evidence that the CUL4-DDB1 ligase plays multiple roles in the DNA damage response. We, and others, have shown that the DNA-damage-induced degradation of CDT1 or Spd1 is absolutely dependent on the human (CUL4-DDB1-DTL) or S. pombe (Pcu4-Ddb1-Cdt2) versions of the DTL-containing complex (Liu et al 2005;Higa et al 2006;Jin et al 2006). Additionally, CUL4-DDB1 ligases that include two other substrate recognition proteins, CSA or DDB2, are also modulated by DNA damage and play essential roles in the repair of ultraviolet (UV)-damaged DNA.…”
Section: Dtl Is Required For the Early G2/m Dna Damage Checkpointmentioning
confidence: 78%
See 2 more Smart Citations
“…We favor the former model because there is strong evidence that the CUL4-DDB1 ligase plays multiple roles in the DNA damage response. We, and others, have shown that the DNA-damage-induced degradation of CDT1 or Spd1 is absolutely dependent on the human (CUL4-DDB1-DTL) or S. pombe (Pcu4-Ddb1-Cdt2) versions of the DTL-containing complex (Liu et al 2005;Higa et al 2006;Jin et al 2006). Additionally, CUL4-DDB1 ligases that include two other substrate recognition proteins, CSA or DDB2, are also modulated by DNA damage and play essential roles in the repair of ultraviolet (UV)-damaged DNA.…”
Section: Dtl Is Required For the Early G2/m Dna Damage Checkpointmentioning
confidence: 78%
“…Given these facts, we hypothesized that DTL is required for CDT1 inhibition during S phase. This hypothesis was supported by the recent finding that Cdt2 (the S. pombe DTL homolog) is required for the Pcu4-Ddb1 E3 ubiquitin ligase (the S. pombe equivalent of CUL4-DDB1) to ubiquitinate an inhibitor of ribonucleotide reductase called Spd1 during S phase and after DNA damage (Liu et al 2005). Therefore, we hypothesized that DTL is a component of the CUL4-DDB1 complex required for CDT1 ubiquitination.…”
Section: Dtl Associates With the Cul4a-ddb1 E3 Ubiquitin Ligasementioning
confidence: 80%
See 1 more Smart Citation
“…As it has been shown, CSN-mediated deneddylation prevents the assembly of a specific CRL [4]. In cooperation with the UPS the CSN participates in processes such as DNA repair [7], cell cycle [8], angiogenesis [9] and development [10][11][12]. However, its role in apoptosis is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…21 Spd1 and Epe1 accumulate in cells lacking Ddb1, Cdt2 or with defective COP9, inducing defects in cell cycle and in heterochromatin silencing. Since the defects in cell cycle are largely rescued by deletion of the ribonucleotide reductase inhibitor, Spd1, 22,23 we hypothesized that these strains could have an increased basal activation of the DNA-synthesis checkpoint. One of the consequences of activating Cds1, the effector kinase of this checkpoint, is the phosphorylation of Yox1.…”
Section: Cop9/signalosome Mutants Have Induced Mbf Activitymentioning
confidence: 99%